The Effect of Information, Education, and Communication on Compliance with Multiple Micronutrient Supplements Consumption in Pregnant Women - Nurul Wahidatil Yusro Islami; Rifzul Maulina (KHD Production, 2026)
Multiple micronutrient supplements (MMS) are widely recommended during pregnancy to prevent anemia and improve maternal nutritional status. Despite their proven benefits, adherence to MMS intake among pregnant women remains suboptimal, contributing to the persistently high prevalence of maternal anemia in many low- and middle-income countries. Effective Information, Education, and Communication (IEC) delivered by health workers may play a crucial role in improving maternal knowledge and adherence to supplementation. This study aimed to examine the association between the quality of IEC provided by health workers and compliance with MMS consumption among pregnant women. A cross-sectional study was conducted involving 30 pregnant women selected through a total sampling method. Data were collected using validated and reliable questionnaires measuring the quality of IEC and adherence to MMS intake. Descriptive statistics were used to summarize participant characteristics, and the association between IEC quality and MMS compliance was analyzed using the Chi-square test. Odds ratios (OR) were calculated to estimate the strength of the relationship. The majority of respondents received high-quality IEC (63.3%), and 66.7% of pregnant women reported compliance with MMS consumption. Statistical analysis revealed a significant association between IEC quality and MMS compliance (p = 0.012). Pregnant women who received high-quality IEC were 10.5 times more likely to adhere to MMS intake compared with those who received poor-quality IEC (OR = 10.5). The quality of Information, Education, and Communication (IEC) significantly influences pregnant women’s compliance with MMS consumption. Strengthening structured, interactive, and continuous IEC during antenatal care is recommended to improve adherence to supplementation and ultimately enhance maternal nutritional outcomes.